Cardiovascular Supportive Therapies for Neonates With Asphyxia — A Literature Review of Pre-clinical and Clinical Studies - Joynt, Chloe; Cheung, Po-Yin (Frontiers in Pediatrics, 2018)
Asphyxiated neonates often have hypotension, shock, and poor tissue perfusion. Various “inotropic” medications are used to provide cardiovascular support to improve the blood pressure and to treat shock. However, there is incomplete literature on the examination of hemodynamic effects of these medications in asphyxiated neonates, especially in the realm of clinical studies (mostly in late preterm or term populations). Although the extrapolation of findings from animal studies and other clinical populations such as children and adults require caution, it seems appropriate that findings from carefully conducted pre-clinical studies are important in answering some of the fundamental knowledge gaps. Based on a literature search, this review discusses the current available information, from both clinical studies and animal models of neonatal asphyxia, on common medications used to provide hemodynamic support including dopamine, dobutamine, epinephrine, milrinone, norepinephrine, vasopressin, levosimendan, and hydrocortisone.